Miniaturization of Resonator based on Moore Fractal - E. Mohd; S. H. Dahlan (Universitas Ahmad Dahlan, 2017)
This paper presents the simulation and fabrication of miniaturized half wavelength resonator design using Moore fractal iteration technique. These resonators have been prepared for wireless application at a centre frequency of 2.45GHz using a substrate with dielectric constant of 2.2. The size and performance are compared with the conventional half wavelength open line resonator. It can be shown that the Moore fractal iteration technique able to reduce 46% of the size of conventional half wavelength resonator through first iteration, and 30% through second iteration while maintaining the resonance performance. The resonators have been fabricated using conventional printed circuit board facilities not specialized in microwave devices. However, the unloaded Q-value of the Moore structure generally much lower compared the open line type.